Digital entrepreneurial acceptance: An examination of technology acceptance model and do-it-yourself behavior - Muhammad Ilyas; Arif Ud Din; Muhammad Haleem; Irshad Ahmad (Journal of Innovation and Entrepreneurship, 2023)
The study extended the existing literature on digital entrepreneurship, do-it-yourself and technology acceptance models with the help of empirical data. It further aimed to identify the factors associated with the e-entrepreneurial acceptance by examining the integration of do-it-yourself and technology acceptance models. A data sample consisting of 200 questionnaires were collected from small-medium enterprise using the digital platforms for their business activities. Structural equation modeling was applied for testing the association of the models. A robust theoretical framework adopted to validate to use digital entrepreneurship as a standalone or along with the traditional entrepreneurial. The study was only limited to the small-medium enterprises working in the context of Pakistan. A total of 200 respondents were visited to collect the data using convenience sampling technique. The findings of this study concluded that all the variables of technology acceptance model are significantly related to the digital entrepreneurial acceptance. Similarly, factors associated with do-it-yourself behavior had a substantial influence, with the exception of perceived lack of product quality as well as perceived lack of product availability variables, which had no significant impact on digital entrepreneurial acceptance.
Keywords: 650; Digital entrepreneurship; Do-it-yourself; Small~and~medium-sized enterprises; Technology acceptance model